2016
DOI: 10.1007/s40592-016-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial replacement techniques: egg donation, genealogy and eugenics

Abstract: Several objections against the morality of researching or employing mitochondrial replacement techniques have been advanced recently. In this paper, I examine three of these objections and show that they are found wanting. First I examine whether mitochondrial replacement techniques, research and clinical practice, should not be carried out because of possible harms to egg donors. Next I assess whether mitochondrial replacement techniques should be banned because they could affect the study of genealogical anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A number of challenges have been made to MRT on legal and ethical grounds 43,[74][75][76][77] . These include the objection that there are safe alternatives for affected women if they relinquish the requirement for genetic relatedness.…”
Section: Social and Regulatory Challengesmentioning
confidence: 99%
“…A number of challenges have been made to MRT on legal and ethical grounds 43,[74][75][76][77] . These include the objection that there are safe alternatives for affected women if they relinquish the requirement for genetic relatedness.…”
Section: Social and Regulatory Challengesmentioning
confidence: 99%
“…(2019) reported that mutations in mt-DNA are responsible for 10–15% of mitochondrial diseases. It should be noted that mitochondrial dysfunction results from a mutation in both mt-DNA and nDNA ( Palacios-Gonzalez, 2016 ). Some of the diseases associated with mitochondrial dysfunction are given in Table1 .…”
Section: Mitochondrial Disordersmentioning
confidence: 99%
“…It also does not ensure prevention ( Klopstock et al., 2016 ). While providing eggs to patients, the harm-benefit ratio is not sufficiently commendable for the continuation of the procedure ( Palacios-Gonzalez, 2016 ). The procedure typically results in a wide variety of heteroplasm loads in newborns plodding up the effects ( Gemmell and Wolff, 2015 ).…”
Section: Exaggerated Criticismmentioning
confidence: 99%
“…There is, however, no moral difference between MST and PNT when examined from the somatic/germline optic. This is so as both can be instances of germline interventions and of somatic interventions (Palacios-González 2016 , p. 47–48; Institute of Medicine of the National Academies 2016 , p. 89; Bredenoord et al 2011 , p. 100).…”
Section: Germline/somatic Interventionsmentioning
confidence: 99%